Effects of virtual reality-based training and task-oriented training on balance performance in stroke patients - Lee, Hyung Young; Lee, Suk Min; Kim, You Lim (Journal of Physical Therapy Science, 2015)
[Purpose] This study aimed to investigate the clinical effects of virtual reality-based training and task-oriented training on balance performance in stroke patients. [Subjects and Methods] The subjects were randomly allocated to 2 groups: virtual reality-based training group (n = 12) and task-oriented training group (n = 12). The patients in the virtual reality-based training group used the Nintendo Wii Fit Plus, which provided visual and auditory feedback as well as the movements that enabled shifting of weight to the right and left sides, for 30 min/day, 3 times/week for 6 weeks. The patients in the task-oriented training group practiced additional task-oriented programs for 30 min/day, 3 times/week for 6 weeks. Patients in both groups also underwent conventional physical therapy for 60 min/day, 5 times/week for 6 weeks. [Results] Balance and functional reach test outcomes were examined in both groups. The results showed that the static balance and functional reach test outcomes were significantly higher in the virtual reality-based training group than in the task-oriented training group. [Conclusion] This study suggested that virtual reality-based training might be a more feasible and suitable therapeutic intervention for dynamic balance in stroke patients compared to task-oriented training.